Antibacterial Activity of Modified Carbon Sorbents, Prospective for Application - V. T. Dolgikh; L. G. Pyanova; E. V. Naumkina; A. V. Lavrenov; E. V. Matushchenko; N. V. Kornienko (Антибиотики и Химиотерапия, 2020)
The aim of the work is to study the antibacterial and antimycotic properties of carbon sorbents modified with biologically active substances in relation to pathogens of purulent-inflammatory diseases. Material and methods. The activity of modifier solutions and modified samples of carbon sorbents was studied in relation to test strains of opportunistic microorganisms in comparison with the initial sample of carbon sorbent. A suspension with a known content of microbial cells was prepared from test strains of microorganisms; it was incubated in wells with test samples for 48 hours. The survival of microorganisms was determined by quantitative inoculation from each well of the sample and microorganism mixture at regular intervals of incubation on Petri dishes with simple agar nutrient, then the number of viable microbial cells in the test mixture was counted. Results. Studies have shown high antibacterial and antimycotic activity of modified carbon sorbents. The best result in comparison with the initial sample was demonstrated by a carbon sorbent modified with lactic acid oligomers and immobilized lysozyme. Studies have shown the promise of using modified carbon sorbent samples for the application therapy in bacterial infections.